Strategi Manajemen Public Relations Starbucks dalam Pemulihan Reputasi Merek Pasca Krisis Global 2024–2026 - Nisa Mukti Rahayu; Lidya Imas Ayu; Marjam Desma Rahadhini (CV. Aksara Global Akademia, 2026)
The dynamics of the global coffee industry during the 2024–2026 period were characterized by significant fluctuations that placed Starbucks in a vulnerable position due to multidimensional reputation crises, ranging from geopolitical sentiments to industrial relations tensions. This study aims to analyze the effectiveness of Public Relations (PR) management strategies and integrated media models in restoring brand equity post-crisis. The research method applied is descriptive qualitative with a conceptual analysis approach, relying on digital literature studies and the collection of secondary data from international reputation research firm reports and credible mass media documentation. The research results indicate that the drastic decline in the Brand Strength Index was successfully mitigated through a strategic narrative transition from service efficiency toward the reinforcement of the original